The Implied Reader and the Recovery of Childhood: - Rizk, Georgette Talaat (AUC Knowledge Fountain, 2019)

(untitled)
This thesis argues that J.R.R. Tolkien's The Hobbit uses a storyteller-narrator and a child/adult implied reader to guide child readers towards maturity and allow adult readers to reengage with the world of childhood. The storyteller replicates traditional fairytale and epic storytelling, a tradition which simultaneously engages adults and children. The novel's language, intertexts, themes, humor and the reader's encouraged identification with the hobbit, Bilbo, suggest that the implied reader is both an adult and a child. The novel invites the reader to adopt Bilbo's development of a childlike perspective valuing the immaterial over the material. The life-like nature of time in the novel facilitates the reader's engagement with moral questions posed by the text which leads to Recovery: the adult's return to the pure view of childhood. The Christian concept of one's rebecoming a child as essential to a person's spiritual and moral development is shown to have inspired the construction of the novel's child/adult implied reader.